Mechanical ventilation induces lung and brain injury through ATP production, P2Y1 receptor activation and dopamine release. Issue 2 (1st February 2022) - Wei, Wei; Sun, Zhentao; He, Shifeng; Zhang, Wanyue; Chen, Sai; Cao, Ya-Nan; Wang, Ning
ABSTRACT: Mechanical ventilation can induce lung injury and exacerbate brain injury due to lung-brain interaction. The current study sought to investigate the mechanism of lung-brain interaction induced by mechanical ventilation and offer theoretical insight into the management of ventilator-induced brain injury. The experimental mice were assigned into the spontaneously breathing group and the mechanical ventilation group and injected with dopamine (DA) receptor antagonist haloperidol or P2Y1 receptor antagonist MRS2279 before ventilation. In vitro assay was conducted using lung epithelial cells MLE-12 hippocampal neuron cells and HT-22. Mouse recognition function and lung injury were examined. The condition and concentration of neurons in the hippocampus were observed. The levels of several inflammatory factors, DA, adenosine triphosphate (ATP), P2Y1R, and dysbindin-1 were detected. Mechanical ventilation induced lung and brain injury in mice, manifested in increased inflammatory factors in the bronchoalveolar lavage fluid and hippocampus, prolonged escape latency, and swimming distance and time in the target quadrant with a weakened concentration of neurons in the hippocampus. Our results presented elevated ATP and P2Y1R expressions in the mechanically ventilated mice and stretched MLE-12 cells. The mechanically ventilated mice and P2Y1 receptor activator MRS2365-treated HT-22 cells presented with elevated levels of DA and dysbindin-1. Inactivation of P2Y1 receptor in the hippocampus or blockage of DA receptor alleviated brain injury induced by mechanical ventilation in mice. To conclude, the current study elicited that lung injury induced by mechanical ventilation exacerbated brain injury in mice by increasing ATP production, activating the P2Y1 receptor, and thus promoting DA release.